The use of technology to enable school governors to participate remotely in meetings: A solution to skilled governor shortages in schools?. (July 2019) - Dobson, Tom; Rose, Anthea
Governor recruitment in England is increasingly difficult, with schools in remote locations struggling to recruit skilled governors. Set against a global context of e-governing, this article evaluates Lloyds Banking Group's (LBG) potential solution – volunteer LBG employees who attend governing board meetings remotely. Interview data collected from five governors and key school stakeholders is analysed using Young's (2017) categorization of governor knowledge as 'managerial', 'educational' and 'lay'. Schools value governors' managerial knowledge more than the governors do, and this is owing to the difficulties governors face in acquiring both 'educational' and 'lay' knowledge – a problem exacerbated by technology and outdated practices. This article recommends ways in which remote attendance of governor meetings could be improved in order to provide a more effective solution to skilled governor recruitment shortages.